Beyond cAMP: The Regulation of Akt and GSK3 by Dopamine Receptors - Beaulieu, Jean-Martin; Del' Guidice, Thomas; Sotnikova, Tatiana; Lemasson, Morgane; Gainetdinov, Raul (Frontiers in Molecular Neuroscience, 2011)
Brain dopamine receptors have been prefered targets for numerous pharmacological compounds developed for the treatment of various neuropsychiatric disorders. Recent discovery that D2 dopamine receptors, in addition to cAMP pathways, can engage also in Akt/GSK3 signaling cascade provided a new framework to understand intracellular signaling mechanisms involved in dopamine-related behaviors and pathologies. Here we review a recent progress in understanding the role of Akt, GSK3 and related signaling molecules in dopamine receptor signaling and functions. Particularly, we focus on the molecular mechanisms involved, interacting partners, role of these signaling events in the action of antipsychotics, psychostimulants and antidepressants as well as involvement in pathophysiology of schizophrenia, bipolar disorder and Parkinson’s disease. Further understanding of the role of Akt/GSK3 signaling in dopamine receptor functions could provide novel targets for pharmacological interventions in dopamine-related disorders.